Pupuk Organik Cair “Eazy Green” Hasil Bio Fertilizer dari Limbah Sayuran Bernilai Ekonomis sebagai Upaya Pelestarian Lingkungan - Muzzazinah Muzzazinah; Karmila Dewi Santika; Mardhiyah Ayu Astari; Maslakhatul Ummah; Mila Nur Annisa; Nidaul Muzayyanah; Nisa Fathin Muslimah; Novi Dwi Apsari; Nurmawati Nurmawati; Rahayu Sulistyowati; Rara Sita Rosa; Restu Setiaji (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The Saribumi Farmers Group is a community of vegetable and tobacco farmers in Cepogo Village. In agricultural activities, farmers still rely on chemical fertilizers which are relatively expensive and have the potential to damage soil quality. Crop failure during the rainy season causes vegetables to rot and are simply thrown away. Meanwhile, the vegetables that have been harvested are then sorted at Cepogo Market and the remaining sorting results become waste that accumulates and pollutes the environment. One alternative that can be done is by processing the waste into liquid organic fertilizer. This Leadership Project aims to educate and empower the Saribumi Farmers Group and the community around Cepogo Market in making liquid organic fertilizer from vegetable waste as well as educating the community on how to package and market fertilizer as an effort to increase income. Activity methods include activity planning, socializing the benefits of liquid organic fertilizer for the environment and its marketing, training on processing vegetable waste through a fermentation process to produce liquid organic fertilizer as a soil biofertilizer, and evaluating the effectiveness of training through results monitoring activities. The result of this activity is increased knowledge of members of the Saribumi Farmers Group and the community around Cepogo Market regarding the use and processing of vegetable waste as material for making liquid organic fertilizer which has economic value. The conclusion from this activity is that it can have a positive impact on farmers' knowledge and skills regarding liquid organic fertilizer.